MEKANISME PEMISAHAN PERKARA (SPLITSING) OLEH JAKSA PENUNTUT UMUM DALAM PROSES PEMBUKTIAN OLEH SAKSI MAHKOTA - Martina Nencylia Riwu Lobo; Simplexius Asa; A Resopijani (Petitum Law Journal, 2026)
This research examines the mechanism of case splitting (splitsing) by the Public Prosecutor and the use of the crown witness (kroon getuige) in the Indonesian criminal justice system. Splitsing is the prosecutor's authority under Article 142 of the Criminal Procedure Code (Code of Criminal Procedure) to split a single case file with multiple suspects into separate prosecutions. This practice is commonly applied in cases of criminal participation (deelneming) or when there is a lack of evidence, particularly witnesses, to facilitate the evidentiary process. The main consequence of splitsing is the emergence of a crown witness, where one defendant is made a witness to provide testimony against another defendant. This term is not explicitly regulated in the Code of Criminal Procedure, but its existence is recognized in judicial practice and supported by Supreme Court jurisprudence. Although considered effective, the use of a crown witness is highly controversial as it is deemed to conflict with human rights and fundamental legal principles. This includes violations of the right against self-incrimination and the principle of a speedy, simple, and low-cost trial. Juridically, a crown witness's testimony can be considered valid evidence if delivered under oath in court. However, its evidentiary strength is discretionary and depends entirely on the judge's assessment and conviction, and it must be supported by other valid evidence.